SOSIALISASI INTEGRASI PSYHCOLOGIES, OPPORTUNITIES DAN CHALLENGES DALAM PENDIDIKAN KEAGAMAAN KATOLIK DI PERBATASAN MALAYSIA - Cenderato, Cenderato; Ahen, Lukas; Bhakti, Angga Satya; Rina, Flariana (STKIP Persada Khatulistiwa Sintang, 2024)
ABSTRACTThe goal of this Community Service Activity (PkM) is to increase awareness among Catholics living in border regions about the significance of Catholic religious education, by reaching out and showcasing the various opportunities for faith formation and education available through Catholic religious education in Malaysia's border areas. This activity utilizes a socialization approach through lectures and presenting material to help people comprehend and become aware of the significance of Catholic religious education. The community appeared highly enthusiastic in carrying out this PkM, as evidenced by the lively discussions between resource persons and participants. The audience raised numerous inquiries and gave feedback on the information presented by the speaker. Typically, individuals experience a sense of peace following prayer, however, there is still a shortage in comprehension of Catholic prayers. Religious ceremonies are forms of support that the Catholic Church specifically, as well as the government in general, can offer. The community benefits from educational staff like monthly visiting priests, teachers, as well as facilities like churches and schools. Many essential services, like repairing damaged roads and providing counseling, should still be effectively managed by the government.Keywords: Psyhcologies, Opportunities, ChallengesABSTRAKTujuan Kegiatan Pengabdian kepada Masyarakat (PkM) ini adalah untuk memberi penyadaran kepada umat Katolik di wilayah perbatasan akan pentingnya pendidikan keagamaan Katolik melalui sosialisasi serta menyoroti peluang pembinaan dan pendidikan iman melalui pendidikan agama Katolik di wilayah perbatasan Malaysia. Kegiatan ini menggunakan pendekatan berupa sosialisasi yaitu dengan cara ceramah dan pemaparan materi dengan maksud memberikan pemahaman yang baik dan penyadaran umat agar memberi perhatian yang penuh akan pentingnya pendidikan keagamaan Katolik. Dalam pelaksanaan PkM ini masyarakat terlihat sangat antusias, hal ini terlihat dari dialog anatara narasumber dengan peserta yang terjadi begitu intens. Masyarakat banyak mengajukan pertanyaaan maupun mengomentari materi-materi yang diberikan oleh narasumber. Secara umum masyarakat mersakan tenang setelah berdoa namun disis lain pemahaman mengenai doa-doa katolik masih kurang. Pelayanan keagamaan merupakan tindakan perhatian yang dapat diberikan Gereja Katolik secara khusus dan juga oleh pemerintah secara umum. Pelayanan yang sudah diterima masyarakat disana ialah tersebut ketersediaan tenaga pendidik, seperti kunjungan Imam sebulan sekali, guru, dan fasilitas seperti Gereja, sekolah. Masih banyak pelayanan yang seharusnya maksimal dapat disediakan oleh pemerintah seperti jalan rusak yang harus diperbaiki untuk memudahkan pelayanan dan juga seperti penyuluhan yang dapat dilakukan oleh pemerintah setempat.Kata Kunci:, Psikologi, Peluang, Tantangan